Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Produk Kosmetik Pada Gen-Z di Purbalingga - Anisa Nur Fadilah; Erny Rachmawati; Muchammad Agung Miftahuddin; Nawalin Nazah (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of brand image, lifestyle, product quality, and advertising on Generation Z’s purchasing decisions for OMG cosmetics in Purbalingga Regency. Using a quantitative survey approach, data from 125 respondents were collected via questionnaires with a 5-point Likert scale. Purposive sampling and the Lemeshow formula determined the sample. SPSS 27 was used for analysis. Results indicate brand image, lifestyle, and advertising significantly influence purchasing decisions. The findings highlight the strategic role of these variables in shaping consumer behavior toward OMG products among Generation Z in Purbalingga.